Pendampingan Asuhan Keperawatan Medikal Bedah pada Pasien dengan Gangguan Sistem Kardiovaskular (Hipertensi) di Wilayah Kerja Puskesmas Cijeungjing - Moch Rully Efendi (Yayasan Inspirasi El Burhani, 2022)
Introduction: Hypertension or high blood pressure is a condition when the blood pressure is at 130/80 mmHg or more. Causes of hypertension are divided into primary hypertension and secondary hypertension. Secondary hypertension has no known cause with certainty, while secondary hypertension can occur, among others, due to kidney disease, sleep apnea, and alcohol addiction. Objective: This assistance aims to provide nursing care to Mrs. M with a medical diagnosis of hypertension at the Cijeungjing Public Health Center in 2021. Method: Assistance activities are carried out by providing nursing care through 5 stages of the nursing process, including Assessment, Diagnosis, Nursing Intervention, Nursing Implementation, and Evaluation Result: The results of the study showed that the patient's main complaint was headache, the diagnosis that appeared in the patient was acute pain, after being given nursing actions from December 22, the patient said the pain had decreased. Conclusion: After the process of providing nursing care was carried out on December 22, 2021, the nursing problems found in Ny. M with a medical diagnosis of hypertension can be resolved.